Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Guru Yang Dimediasi Oleh Kemampuan Kerja (Studi Pada SMPI Miftahul Ulum Tambelangan Kabupaten Sampang) - Fahri Alamsyah; Chamariyah Chamariyah; Ruddy Winarko (Universitas 45 Surabaya, 2023)
Fahri Alamsyah, 2023. The Effect Of Work Ability And Work Discipline On The Performance Of Employees In Gan The Influence of Work Motivation and Discipline on Teacher Performance Mediated by Work Ability (Studies at SMPI Miftahul Ulum Tambelengan, Sampang Regency. Postgraduate Program at Wijaya Putra University, Surabaya. This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 42 teachers. The aims of this study were 1) to test and analyze whether motivation has a significant effect on teacher performance at SMPI Miftahul Ulum Tambelangan, Sampang Regency. 2) To test and analyze whether work discipline has a significant effect on teacher performance at SMPI Miftahul Ulum Tambelangan, Sampang Regency. 3) To test and analyze whether motivation has a significant influence on work ability at SMPI Miftahul Ulum Tambelangan, Sampang Regency. 4) To test and analyze whether work discipline has a significant effect on work ability at SMPI Miftahul Ulum Tambelangan, Sampang Regency. 5) To test and analyze whether work ability has a significant effect on teacher performance at SMPI Miftahul Ulum Tambelangan, Sampang Regency. 6) To test and analyze whether motivation has an indirect influence on teacher performance at SMPI Miftahul Ulum Tambelangan, Sampang Regency, which is mediated by work ability. 7) To test and analyze whether work discipline has an indirect influence on teacher performance at SMPI Miftahul Ulum Tambelangan, Sampang Regency, which is mediated by work ability. The results showed that: 1) Motivation had a significant positive effect on teacher performance at SMPI MIftahul Ulum Tambelengan, Sampang Regency with an original sample value of 0.092. 2) Work discipline has a significant positive effect on teacher performance at SMPI MIftahul Ulum Tambelengan, Sampang Regency with an original sample value of 0.378. 3) Motivation has a significant positive effect on the work ability of MIftahul Ulum Tambelengan Middle School, Sampang Regency with an original sample value of 0.356. 4) Work discipline has a significant positive effect on the work ability of MIftahul Ulum Tambelengan Middle School teachers in Sampang Regency with an original sample value of 0.300. 5) Work ability has a significant positive effect on teacher performance at SMPI MIftahul Ulum Tambelengan, Sampang Regency with an original sample value of 0.322. 6) Motivation has a significant positive effect on teacher performance which is mediated by the work ability of MIftahul Ulum Tambelengan Middle School teachers, Sampang Regency with an original sample value of 0.1144. 7) Work discipline has a significant positive effect on teacher performance which is mediated by the work ability of MIftahul Ulum Tambelengan Middle School teachers, Sampang Regency with an original sample value of 0.147.